Fast and tiny: A model for the flame propagation of nanopowders. (July 2021) - Santandrea, Audrey; Torrado, David; Pietraccini, Matteo; Vignes, Alexis; Perrin, Laurent; Dufaud, Olivier
Abstract: To avoid the influence of external parameters, such as the vessel volume or the initial turbulence, the explosion severity should be determined from intrinsic properties of the fuel-air mixture. Therefore, the flame propagation of gaseous mixtures is often studied in order to estimate their laminar burning velocity, which is both independent of external factors and a useful input for CFD simulation. Experimentally, this parameter is difficult to evaluate when it comes to dust explosion, due to the inherent turbulence during the dispersion of the cloud. However, the low inertia of nanoparticles allows performing tests at very low turbulence without sedimentation. Knowledge on flame propagation concerning nanoparticles may then be modelled and, under certain conditions, extrapolated to microparticles, for which an experimental measurement is a delicate task. This work focuses on a nanocellulose with primary fiber dimensions of 3 nm width and 70 nm length. A one-dimensional model was developed to estimate the flame velocity of a nanocellulose explosion, based on an existing model already validated for hybrid mixtures of gas and carbonaceous nanopowders similar to soot. Assuming the fast devolatilization of organic nanopowders, the chemical reactions considered are limited to the combustion of the pyrolysis gases. The finite volume method was used to solve the mass and energy balances equations and mass reactions rates constituting the numerical system. Finally, the radiative heat transfer was also considered, highlighting the influence of the total surface area of the particles on the thermal radiation. Flame velocities of nanocellulose from 17.5 to 20.8 cm/s were obtained numerically depending on the radiative heat transfer, which proves a good agreement with the values around 21 cm/s measured experimentally by flame visualization and allows the validation of the model for nanoparticles. Highlights: A 1D model was developed to estimate the laminar flame velocity of nanocellulose. Oxidation reactions of the pyrolysis gases of nanocellulose were considered. Influence of the total surface area of particles on the thermal radiation is shown. Laminar flame velocities of nanocellulose ranges from 17.5 to 20.8 cm s −1